Effect of nickel ion concentration on structural, optical and electrical properties towards Ni–H3BTC-MOF formation for nonlinear saturable absorption phenomenon. (August 2022) - Murad, A.; Liew, J.Y.C.; Yaacob, M.H.; Noor, I.M.; Osman, N.H.; Kamarudin, M.A.; Tan, S.T.; Lee, H.K.; Talib, Z.A.; Alresheedi, M.T.; Mahdi, M.A.
Abstract: Metal-organic frameworks (MOFs) are a class of crystalline hybrid porous materials that have drawn considerable research interest owing to their tunable characteristics and wide range of applications. In this study, we investigated the effect of the nickel ion concentration on the structural, optical, and electrical properties of Ni–H3 BTC-MOF for the potential nonlinear saturable absorbance phenomenon. Structural analysis was performed using Fourier transform infrared spectroscopy, X-ray diffraction and Brunauer–Emmett–Teller analysis, whereas diffuse reflectance UV–Vis–NIR spectroscopy was used to characterize the optical properties. The AC transport properties of the as-prepared Ni–H3 BTC-MOF were investigated using electrical impedance spectroscopy. It was found that the porosity increased with an increasing concentration of nickel ions. In contrast, the real permittivity and loss tangent decreased. The highest modulation depth obtained was 4.48% for the sample with a nickel ion concentration of 2 mmol. This performance has been attributed to the low loss tangent (0.06–0.26), low real permittivity (11.3–23.9) F/m, median porosity (7.08 nm) and layered flower-shaped morphology of the material, all of which are desirable for the nonlinear saturable absorbance phenomenon. Highlights: Synthesis of Ni–H3 BTC-MOF via effect of nickel ion concentration. The primitive fundamental study of Ni–H3 BTC-MOF for photonics applications. Non-linear properties of the Ni–H3 BTC-MOF elucidated with the structural, optical and electrical properties. Ni–H3 BTC-MOF as the promising and stable NLSA material as it generates a modulation depth of 4.48%.